De-Serbianising of Serbian Nation and Change of Identity in a Globalized Society - Anđelkovic, Petar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
One of the terms of preserving the identity of each community is the continuity of cultural heritage, that is, to have an aware and active attitude towards the tradition which confirms what is unchanging and permanent. Discontinuities, which Serbian people have often suffered as a result of ideological and political manipulation, brought about personal and collective oblivion and abolishing of its own identity. In severe and unfavorable historical circumstances, under compulsion and indoctrination, Serbs were forced to accept another religion that led to de-serbianising, which in most cases resulted in the Serbs becoming members of other ethnic and national communities. This process of Serbian compliance then led to this oblivion, happening mostly as an act of coercion and blackmail, aimed at preservation of bare physical existence. What is happening today, in a globalized society, has a completely different character. With the intention of enforcing the Serbian sovereignty to accept its subordination to the West in the context of the global system, all relevant national institutions are destroyed. In addition, factors of collective national identity were compromised, thus performing a de-serbianisation which leads to the change of identity. Of course, if we neglect ourselves, if we strive to change our identity by negating what we have been, we will not become someone else, but we will annul the one thing that denotes us. The national wisdom, at the time of slavery under the Turks, pronounced and gave the Serb ancestor an imperative: even though we have lost the empire, we will not lose our souls! (From the folk song, the Turks will not drink to the glory of God). Today, when we are increasingly embroiled in new bondage, let us not forget this imperative and fail our ancestors. A nation that renounces its past, a nation that lets it be forgotten, is on a sure path into the abyss.